Adaptation to Climate Change Urban Heat Island Effect and Its Challenges in Urban Settlement - Ar. Shivani Singh Ghuraiya (Calibrating Urban Livability in the Global South, 2024)
Climate change is a big problem for cities around the world, and it’s getting worse. Even though we’re trying to stop it, some changes are already happening and will continue. Cities are especially at risk from things like more rain, bigger storms, floods, and very hot temperatures, which can make city life difficult. We need to start preparing our cities to handle these challenges better. Nature has been balancing itself for billions of years, but since the Industrial Revolution, we’ve been throwing off this balance. Now, with more heatwaves that can make people very sick, we have to change how we live and use our spaces to deal with climate change. Yet, amidst these challenges, there lies a solution embedded in the realm of data-informed policies. Cities can mitigate the urban heat island effect, enhance livability, and promote walkability. A spectrum of strategies is being embraced by forward-thinking cities, from expanding green spaces and integrating urban vegetation to counteracting the urban heat island effect, to championing the use of reflective and permeable surfaces. Sustainable urban planning aims to address immediate concerns and enhance climate resilience, creating comfortable and sustainable environments for residents. India’s urban transformation is crucial for climate mitigation and adaptation, with a significant portion still awaiting development, presenting a unique opportunity to establish low-carbon, resilient, and equitable structures. The paper discusses India’s sustainable urban future, emphasizing low-carbon initiatives, climate resilience, and equity in planning, while addressing the increasing UHI impacting public comfort.